Embroidery - Ganderton, Lucinda (DK, 2015)
"Embroidery" is the ultimate stitch dictionary and the ideal guide to embroidery, whatever your level of expertise. The perfect reference guide to needlework, "Embroidery" is a comprehensive guide to inspire and inform sewers of all levels. Find advice on which thread, needles, or fabrics work with which techniques, and take a look at an incredible 200 stitches with levels of difficulty, step-by-step instructions, and ideas on where and how to use them. This practical guide covers sewing tips for dressmaking, needlepoint, and embroidery stitches, with detailed information simply presented in illustration-rich pages. With "Embroidery" it's easy to find exactly which stitch is right for your next sewing project.